"Overview of Intermaterials Competition" - Thomas Henderson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Strategically, intermaterials competition is important to companies involved in raw materials extraction, smelting, refining or other processing, semi-finished and finished goods fabrication, and end-use consumers. In other words, just about every company involved in manufacturing. The array of materials covered by other papers in this session is testimony to the subject's breadth. In trying to provide an over- view of such a broad topic, the purpose has been to relate some of the common characteristics of the markets, economics and technology of raw materials, and to describe some of the ways in which Intermaterials competition impacts the markets, economics and technology of raw materials.